Paciente de sexo femenino de 71 años de edad con hipotiroidismo y obesidad. - Del Salto Águila, Katelyn Magdalena (2021)
The present clinical case is about a 71 year-old female patient with hypothyroidism and obesity with a personal pathological history of diabetes, hypertension, and several surgical interventions. She came to the outpatient clinic for presenting in the last weeks an increase in her weight, tiredness, depression and fatigue for no apparent reason. Nutritional status was assessed with anthropometric, dietary, clinical and biochemical methods where TSH alterations were reported with higher than normal values, elevated HDL values above normal, and according to the 24-hour reminder applied to the patient, an eating disorder and excessive consumption of saturated foods and simple carbohydrates were reported. This nutritional intervention was carried out with the aim of applying a dietary therapeutic plan that fits the patient's needs and thus prevent the progression of the disease. As a final point, favorable results were observed in the treatment and nutritional intervention according to the patient's follow-up.